Customer Satisfaction of Indonesian Sharia Bank: Multi Factorial Analysis - Wiharso, Gani; Mulyadi, Hary; Abdullah, Muhammad; Basudani, Wahid Akbar; Simamora, Valentine Theresia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Of the Muslim countries in the world, Indonesia is one of the large countries that has the largest Muslim population. So Indonesia is one of the markets that creates a monetary foundation that relies on the sharia framework, including sharia banking. Furthermore, this provides freedom for sharia banking to offer sharia products to people who want to switch from conventional financial products to sharia banking products, especially products that have often been used by the general public, such as current accounts, savings and deposits. The essence of this exploration is to find out what variables can influence consumer loyalty at BSI Bank Tangerang Karawaci Mutiara branch office. To determine the variables that influence compliance, descriptions are used, especially using illustrative and confirmatory examination methods. The testing procedure used in this exploration was a purposive testing method on 95 respondents. Each naaabah is given a questionnaire with a total of 25 question points, where the questionnaire answers are evaluated on a 1-5 Likert scale and tested using the Smart-PLS 4.0 Application. Based on the results of the tests carried out, it can be said that the variables that influence consumer loyalty are Profit Sharing (X1) and Service Quality (X2) which influence Saving Decisions (Y) and Customer Satisfaction (Z) at Bank BSI Tangerang Karawaci Mutiara Branch Office, so the hypothesis this is acceptable.